The occurance of oil palm weevil, elaeidobius kamerunicus (order coleoptera) and the productivity of oil palm, elaeis guineensis (Family arecaceae) - Siti Khadijah, Bt Abdul Khalid (Universiti Malaysia Sarawak, UNIMAS, 2013)
Malaysia has the most developed oil palm industry in the world and this affects the overall agriculture development of the country. The oil palm tree in Malaysia is Elaeis guineensis (African oil palm) and the main pollinating agent is Elaeidobius kamerunicus (oil palm weevil). This study was conducted in Bangka Semong oil palm plantation, Kota Samarahan, Sarawak to verify the occurrence of E. kamerunicus in response to the productivity of oil palm. The result from this study showed that there is a low occurrence of male flower inflorescences that anthesis (<1%) from 660 oil palm trees sampled. The occurrence of oil palm weevil is higher in block F compared to A (Mann-Whitney U test). The numbers of fresh fruit bunches sampled were significant different comparing four different blocks (one-way ANOVA). The numbers of weevil presence is positively correlated with the numbers of spikelet based on Spearman Rank Correlation test. However, there are no linear relationships between the presence of weevils and the number of fresh fruit bunches or the average diameter of fruit bunches. The findings of this study could provide the useful information on the relationship between the occurrence of oil palm weevil and productivity. In addition, this study can serve as reference for future studies and knowledge on the biology of these insects which is vital for better management of oil palm yields.